2018
DOI: 10.1029/2018jb016601
|View full text |Cite
|
Sign up to set email alerts
|

Rheological Control of Lateral Growth of the Tibetan Plateau: Numerical Results

Abstract: The collision and continued convergence between the Indian and Eurasian plates in the past ~50 million years has raised the Tibetan Plateau, but whether or not, and how, the plateau has grown laterally remain controversial. Here we show that useful insights can be gained by studying lithospheric deformation across the frontal margins of the Tibetan Plateau. Crossing its northern and eastern sides where the plateau is bounded by the Tarim and Sichuan blocks, the topographic slope is steep and crustal deformatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 94 publications
0
14
0
Order By: Relevance
“…The Sichuan basin is completely encircled on all sides by fold and thrust systems and withstands most of the eastward movement of the Tibetan Plateau along its western flank (Sun & Liu, 2018), where the 2008 Mw 7.9 Wenchuan earthquake ruptured the Longmenshan fault (e.g., Xu et al, 2010) (Figure 1a). The unconformities and missed sedimentary sequences document that the basin has experienced multiple stages of tectonic movements (e.g., Yang et al, 2017; Zhang et al, 2007; Zhu et al, 2016).…”
Section: Geological Settings and Injection Operationsmentioning
confidence: 99%
“…The Sichuan basin is completely encircled on all sides by fold and thrust systems and withstands most of the eastward movement of the Tibetan Plateau along its western flank (Sun & Liu, 2018), where the 2008 Mw 7.9 Wenchuan earthquake ruptured the Longmenshan fault (e.g., Xu et al, 2010) (Figure 1a). The unconformities and missed sedimentary sequences document that the basin has experienced multiple stages of tectonic movements (e.g., Yang et al, 2017; Zhang et al, 2007; Zhu et al, 2016).…”
Section: Geological Settings and Injection Operationsmentioning
confidence: 99%
“…On profile a-a' that crosses through the western Kunlun-Qilian orogen (including Qaidam), a high upper-mantle velocity block beneath the Tarim and Qaidam basins seems overthrusting southwards to the northern Tibetan plateau and forms a dome-shaped Moho offset beneath southern Qaidam. Numerical modelling results (Sun & Liu 2018) showed that different rheological contrasts between the plateau and surrounding blocks caused different ways of lateral growth of the plateau. Therefore, it is not surprising that the Qaidam basin, characterized by higher crustal and upper-mantle velocities, and thus by higher viscosities, behaves like a rigid block when the plateau tries to expand across the KF.…”
Section: Deformation Zonation Of the Tibetan Plateaumentioning
confidence: 99%
“…The Arbitrary Lagrange-Euler (Fullsack, 1995) and the marker-in-cell method (Gerya & Yuen, 2003) were used to solve these equations. The code has been tested and used in the previous studies (Sun, Fan, et al, 2018;Sun & Liu, 2018).…”
Section: /2019tc005512mentioning
confidence: 99%
“…It is important to determine what causes the tectonic differences across the southern and northern segments of the Longmen Shan orogenic belt. Numerical results indicate that large rheological contrasts lead to the formation of the steep topography along the eastern margin of the Tibetan Plateau, and the strain and deformation are more likely to accumulate along the contact boundary (Chen et al, 2013;Sun & Liu, 2018). Therefore, an investigation of the detailed rheological structure can provide clues to the variation in deformation.…”
Section: Introductionmentioning
confidence: 99%